‘Because it’s boring, irrelevant and I don’t like computers’: Why high school girls avoid professionally-oriented ICT subjects - Anderson, Neil; Lankshear, Colin; Timms, Carolyn; Courtney, Lyn (Computers and education, 2008)
The current paper details results from the Girls and ICT survey phase of a three year study investigating factors associated with low participation rates by females in education pathways leading to professional level information and communications technology (ICT) professions. The study is funded through the Australian Research Council’s (ARC) Linkage Grants Scheme. It involves a research partnership between Education Queensland (EQ), industry partner Technology One and academic researchers at ( affiliation removed for review purposes). Respondents to the survey were 1453 senior high school girls. Comparisons were drawn between Takers ( n = 131) and Non Takers ( n = 1322) of advanced level computing subjects. Significant differences between the groups were found on four questions: “The subjects are interesting”; “I am very interested in computers”; “The subject will be helpful to me in my chosen career path after school”; and “It suited my timetable”. The research has demonstrated that senior high school girls tend to perceive advanced computing subjects as boring and they express a strong aversion to computers.